Moisture-curable polyethylene composition

A moisture-curable polyethylene composition with a (hydrolyzable silyl group)-functional copolymer and condensation catalyst addresses the challenge of rapid curing and crosslinking, improving cable coating performance by reducing hot creep and enhancing durability.

JP7617847B2Active Publication Date: 2025-01-20DOW GLOBAL TECHNOLOGIES LLC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021555195
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-03-26
Filing Date
2020-02-11
Publication Date
2025-01-20
Estimated Expiration
2040-02-11

AI Technical Summary

Technical Problem

Existing moisture-curable polyethylene compositions face challenges in achieving rapid curing under ambient conditions and sufficient crosslinking, which is crucial for applications like wire and cable coatings, where high hot creep performance is required.

Method used

A moisture-curable polyethylene composition comprising a (hydrolyzable silyl group)-functional polyethylene copolymer and a condensation curing catalyst, allowing for rapid curing under ambient conditions and enhanced crosslinking through immersion in a hot water bath, with specific molecular weight dispersity and hydrolyzable silyl group content optimized for improved performance.

Benefits of technology

The composition achieves fast moisture curing and high crosslinking, ensuring low hot creep performance, thereby enhancing the manufacturing throughput and durability of coated cables.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007617847000001
    Figure 0007617847000001
  • Figure 0007617847000002
    Figure 0007617847000002
  • Figure 0007617847000003
    Figure 0007617847000003
Patent Text Reader

Abstract

A moisture-curable polyethylene composition comprising a (hydrolyzable silyl group)-functional polyethylene copolymer and a condensation cure catalyst. The composition is designed to moisture cure rapidly under ambient conditions. Also disclosed are methods for making and using the same, cured polymer products produced therefrom, and articles containing or produced therefrom.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 62 / 823,889, filed March 26, 2019, the entire disclosure of which is incorporated herein by reference.

[0002] Introduction Moisture-curable polyethylene compositions and related aspects.

[0003] Patents and published patent applications in or relating to this field include US4297310, US4413066, US4446283, US4689369, US4983675, US7834115B2, US8722827B2, US9133331B2, US9221934B2, and US20140127505A1.

[0004] US4689369 and Iwao Ishino et al., Molecular Structure and Electric Breakdown of Ethylene / Silane Copolymers (Japanese J. Appl. Physics, 1991, vol. 30, no. 4, pp. 720-726) report a composition containing 0.05 weight percent dibutyltin dilaurate, which is cured by immersing the composition in water at 80 degrees Celsius. Summary of the Invention [Problem to be solved by the invention]

[0005] A moisture-curable polyethylene composition has been discovered that includes a (hydrolyzable silyl group)-functional polyethylene copolymer and a condensation cure catalyst. The composition is designed to be moisture fast curing under ambient conditions and / or to achieve greater ultimate crosslinking after curing by immersion in a hot water bath. Also discovered are methods of making and using the same, cured polymer products made therefrom, and articles containing or made therefrom. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] A moisture-curable polyethylene composition ("composition" or "inventive composition") comprising a (hydrolyzable silyl group) functional polyethylene copolymer (HSG-FP copolymer) and a condensation cure catalyst. Also provided are methods of making and using same, cured polymer compositions made therefrom, and articles containing or made therefrom.

[0007] The compositions are rapidly moisture curable under ambient conditions, including air atmosphere, ambient temperature (e.g., 20-40 degrees Celsius (°C)), and ambient relative humidity (e.g., 10-96 percent relative humidity (%RH)). The compositions are also designed to achieve a high final degree (hot creep percent ≦175%) or maximum crosslinking after curing by immersion in a hot water bath. The greater the final degree of crosslinking possible in the HSG-FP copolymer, the lower the hot creep percent or the greater the amount of non-crosslinked or non-moisture curable polymers (e.g., peroxide and / or light cured only) (e.g., polymers other than HSG-FP copolymers, such as polyolefins, styrenic polymers, rubbers, etc.) that can be incorporated into the composition without preventing the moisture cured polymer product from achieving satisfactory hot creep performance of ≦175% in wire and cable applications after curing. The faster a hot creep of ≦175% is achieved under ambient conditions, the higher the throughput of a manufacturing operation using the composition to deposit a moisture cured coating layer on a cable. The hot creep percentage of the cured polymer product may be 5%, 10%, 15%, or 20% to 175%, or 50% to 175%, or 100% to 175%, or 150% to 175. These properties are achieved by a combination of the enabling properties of the HSG-FP copolymer and the enabling properties of the composition. The enabling properties of the HSG-FP copolymer include the composition of the HSG-FP copolymer (which is obtained from the process for producing the HSG-FP copolymer (effective process described below)), the hydrolyzable silyl group content of the HSG-FP copolymer (which is obtained from the molar ratio of ethylene monomer to alkenyl functional hydrolyzable silane comonomer in the HSG-FP copolymer (or the molar ratio used in the production process)), and the molecular weight dispersity of the HSG-FP copolymer (which is obtained from the specific conditions of the production process, such as reactor temperature and pressure, the relative amounts of materials in the reactor, etc.). The enabling properties of the composition include the concentration of the HSG-FP copolymer and the condensation cure catalyst therein. These amounts are independently selected to meet or exceed minimum concentrations to allow for rapid moisture cure under ambient conditions and greater ultimate crosslinking of the cured polymer product.

[0008] Some embodiments are numbered for ease of reference.

[0009] Aspect 1.1 A moisture-curable polyethylene composition comprising 5.00 to 99.99 weight percent (wt%) of (A) a (hydrolyzable silyl group)-functional polyethylene copolymer (HSG-FP copolymer), 0.1 to 5 wt%, alternatively 0.010 to 5.0 wt% of a (B) condensation cure catalyst, and a total of 0 to 84.99 wt% of one or more optional additives, wherein when (B) is solely a dialkyltin dicarboxylate (i.e., (B) does not include a non-tin based catalyst), the dialkyltin dicarboxylate is at least 0.10 wt% of the moisture-curable polyethylene composition, and (A) provided that the HSG-FP copolymer is up to 99.90% by weight of the moisture-curable polyethylene composition, all weight percentages being based on total weight and totaling 100.00% by weight of the moisture-curable polyethylene composition; and (A) the HSG-FP copolymer is produced by copolymerizing (polymerizing together) ethylene (monomer), at least one alkenyl-functional hydrolyzable silane (comonomer), optionally propylene (HC=C(H)CH), and optionally an olefinic comonomer, the copolymerization being free of a metal-containing olefin polymerization catalyst and free of one or more organic peroxides, and optionally propylene or (C4-C 20 ) under effective process conditions in a high pressure, high temperature (HPT) reactor containing a chain transfer agent (CTA) that is not an alpha-olefin, (A) the HSG-FP copolymer has a total hydrolyzable silyl group content of 0.38 to 0.99 mole percent (mol%) and a molecular weight dispersity of any one of limits (i) to (iii), i.e.: (i) the ratio of absolute z-average molecular weight to absolute weight average molecular weight (M z(abs) / M w(abs) or absolute molecular weight dispersity) is 9.51 or more, (ii) the ratio of absolute molecular weight dispersity to conventional molecular weight dispersity ((M z(abs) / M w(abs) ) / (M w(conv) / M n(conv) ) is 1.51 or more (Mw(conv) is the conventional weight average molecular weight and M n(conv) is the conventional number average molecular weight), and (iii) both (i) and (ii). The hydrolyzable silyl group content can be determined by X-ray fluorescence (XRF) spectroscopy according to the NMR, FT-IR, or XRF test methods described below. The molecular weight dispersity limits (i)-(iii) can be determined by gel permeation chromatography (GPC) according to the GPC test methods described below. The process conditions include temperature, pressure, and the amount of material in the HPT reactor. The copolymerization is carried out in a manner such that the (A) HSG-FP copolymer produced by the aforementioned process, in combination with the aforementioned concentrations (wt %) of (A) HSG-FP copolymer and (B) condensation cure catalyst in the composition, is characterized by the composition, hydrolyzable silyl group content, and molecular weight dispersity, allowing the composition to be rapidly moisture cured under ambient conditions. The composition may be free of compounds that are alkenyl-functional hydrolyzable silanes and / or compounds that contain grafted hydrolyzable silyl groups.

[0010] The composition of the (A)HSG-FP copolymer produced by the aforementioned process is characterized by constitutional units selected from ethylene units, alkylene hydrolyzable silyl group units, optionally propylene units, and optional comonomer units derived from any olefin comonomer. The copolymerization may be free of any olefin comonomer, and the (A)HSG-FP copolymer may be free of comonomer units derived from any olefin comonomer. Alternatively, the copolymerization may include an olefinic comonomer, and the (A)HSG-FP copolymer may include comonomer units derived from an olefinic comonomer. The olefinic comonomer may be any of the following: (C4-C 20) alpha-olefins, olefinically unsaturated carboxylic acids, olefinically unsaturated carboxylic esters, olefinically unsaturated carboxylic anhydrides, and combinations thereof. The carboxylic acids can be mono- or dicarboxylic acids. The carboxylic esters can be mono-, di- or di-carboxylic acid monoesters, or di-carboxylic acid diesters. The olefinically unsaturated carboxylic acids can be terminally unsaturated (C2-C8) carboxylic acids, or (meth)acrylic acids, or unsaturated dicarboxylic acids. The olefinically unsaturated carboxylic esters can be vinyl (C2-C8) carboxylate esters, or vinyl (C2-C5) carboxylate esters (e.g., vinyl acetate, vinyl propionate, or vinyl butanoate), or (C1-C8) alkyl (meth)acrylate esters. Alternatively, it may be a (C1-C3) alkyl (meth)acrylate ester, or a di(C1-C8) alkyl diester of an unsaturated dicarboxylic acid, or a mono(C1-C8) alkyl ester of an unsaturated dicarboxylic acid, or a mono(C1-C8) alkyl ester of maleic acid. By (meth)acrylate is meant H2C=CHCO2- or H2C=C(CH3)CO2-. The CTA may be acetone, methyl ethyl ketone, propionaldehyde, 2-propanol, ethyl acetate, isobutene, butane, 2-methylpropane, ISOPARTM-C, ISOPARTM-E, ISOPARTM-H, or a combination of any two or more thereof. If present, the CTA may be 0.03 to 10% by weight of the polymerization reaction mixture.

[0011] Embodiment 2.(i)-(xii), namely: (i) the HPT reactor and process to produce the (A) HSG-FP copolymer is free of propylene, and the (A) HSG-FP copolymer is free of propylene units (0 wt%) derived from propylene; (ii) the HPT reactor and process to produce the (A) HSG-FP copolymer is free of propylene, and the (A) HSG-FP copolymer is free of propylene units (0 wt%) derived from propylene; (iii) the HPT reactor and process to produce the (A) HSG-FP copolymer is free of propylene, and the (A) HSG-FP copolymer is free of propylene units (0 wt%) derived from propylene, based on the total mass flow rate of ethylene, at least one alkenyl-functional hydrolyzable silane, and propylene (which functions as a chain transfer agent and / or molecular weight control agent) to the HPT reactor; and the (A) HSG-FP copolymer is free of propylene units (0 wt%) derived from propylene; 20 ) alpha-olefin-free, and (A) HSG-FP copolymer is (C4-C 20 ) contains no units (0 wt%) derived from alpha-olefins, (iv) the HPT reactor and process for producing (A) the HSG-FP copolymer comprises a mixture of ethylene, at least one alkenyl-functional hydrolyzable silane, and (C4-C 20 ) alpha-olefins (e.g., (C4-C8) alpha-olefins) from greater than 0 wt.% up to 20 wt.% (C4-C 20 ) alpha-olefin (e.g., (C4-C8) alpha-olefin), and (A) HSG-FP copolymer comprises from greater than 0 wt.% to a maximum of 20 wt.% (C4-C 20) copolymer units derived from an alpha-olefin (e.g., a (C4-C8) alpha-olefin); (v) both (i) and (iii); (vi) both (i) and (iv); (vii) both (ii) and (iii); (viii) both (ii) and (iv); (ix) (A) the HSG-FP copolymer is free of grafted hydrolyzable silyl groups (free of groups attached to (A) during the post-polymerization reactor grafting process) and the moisture-curable polyethylene composition is free of alkenyl-functional hydrolyzable silanes (unreacted); (x) (ix) and limitations (i) through (viii) (xi) the effective process conditions are characterized by a reactor temperature of from 175° C. to 400.0° C. (e.g., from 180.0° C. to 320° C., alternatively from 200° C. to 300° C., alternatively from 245° C. to 255° C., e.g., 250° C.±1° C.), and a reactor pressure of from 34.5 to 344.7 megapascals (MPa) (e.g., from 110 to 310 MPa, alternatively from 150 to 250 MPa, alternatively from 185 to 195 MPa, e.g., 193 MPa±1.0 MPa); or (xii) both of (xi) and any one of limits (i)-(x).

[0012] Embodiment 3. (A) The HSG-FP copolymer is 0.43 to 0.99 mol%, alternatively 0.48 to 0.99 mol%, alternatively 0.53 to 0.99 mol%, alternatively 0.58 to 0.99 mol%, alternatively 0.63 to 0.99 mol%, alternatively 0.68 to 0.99 mol%, alternatively 0.73 to 0.99 mol%, alternatively 0.78 to 0.99 mol%, alternatively 0.83 to 0.99 mol%, alternatively 0.83 to 0.99 mol%, alternatively 0.38 to 0.99 mol%. 3 mol%, alternatively from 0.38 to 0.88 mol%, alternatively from 0.38 to 0.83 mol%, alternatively from 0.38 to 0.78 mol%, alternatively from 0.38 to 0.73 mol%, alternatively from 0.38 to 0.68 mol%, alternatively from 0.38 to 0.63 mol%, alternatively from 0.38 to 0.58 mol%, alternatively from 0.38 to 0.53 mol%, alternatively from 0.38 to 0.48 mol%, wherein the total mol % hydrolyzable silyl group content is calculated from the weight % values ​​of the hydrolyzable silyl group content, the weight % values ​​being determined according to the X-ray Fluorescence (XRF) testing method described below. For example, if the at least one alkenyl-functional hydrolyzable silane is vinyltrimethoxysilane (VTMS), its molecular weight is 148.23 g / mol, and if the comonomer content is 2.0 wt%, the mol% is 0.38 mol%. If the VTMS comonomer content is 5.0 wt%, the mol% is 0.99 mol%. The mol% hydrolyzable silyl group content at any given wt% hydrolyzable silyl group content value varies inversely with the molecular weight of the at least one alkenyl-functional hydrolyzable silane from which the hydrolyzable silyl group is derived.

[0013] Embodiment 4. (A) The HSG-FP copolymer has an M within limits (i) to (v), i.e.: (i) 10.5 to 21.0, alternatively 12.0 to 20.4, alternatively 14.0 to 20.0, alternatively 16.0 to 19.0, alternatively 16.2 to 18.9. z(abs) / M w(abs) (ii) a (M z(abs) / M w(abs) ) / (M w(conv) / M n(conv) ) ratio (iii) M between 10.5 and 21.0, or between 12.0 and 20.4, or between 14.0 and 20.0, or between 16.0 and 19.0, or between 16.2 and 18.9 z(abs) / M w(abs) and a ratio of 1.9 to 3.4 (M z(abs) / M w(abs) ) / (M w(conv) / M n(conv) ) ratio (iv) M of 10.5 to 21.0 z(abs) / M w(abs) ratio, and (M z(abs) / M w(abs) ) / (M w(conv) / M n(conv) ) ratio, (v) M of 16.2 to 18.9 z(abs) / M w(abs) Ratio, and (M z(abs) / M w(abs) ) / (M w(conv) / M n(conv) 4. The moisture-curable polyethylene composition according to any one of aspects 1 to 3, characterized by a molecular weight dispersity of any one of:

[0014] Embodiment 5. (A) Each hydrolyzable silyl group of the HSG-FP copolymer is independently represented by the formula (R 2 ) m (R 3 ) 3-m is a monovalent radical of Si-, where the subscript m is an integer of 1, 2, or 3, and each R 2 are independently H, HO-, (C1-C8)alkoxy, (C2-C6)carboxy, phenoxy, (C1-C6)alkyl-phenoxy, (C1-C6)alkyl(H)N-, ((C1-C6)alkyl)2N-, (C1-C6)alkyl(H)C=NO-, or ((C1-C6)alkyl)2C=NO-, and each R 3 is independently (C1-C8) alkyl or phenyl. 2 may be free of H and HO-, or free of phenoxy and (C-C) alkyl-phenoxy. 2may be independently (C1-C6)alkoxy, (C2-C6)carboxy, ((C1-C6)alkyl)2N-, (C1-C6)alkyl(H)C=NO-, or ((C1-C6)alkyl)2C=NO-, or (C1-C6)alkoxy, or (C2-C6)carboxy, or ((C1-C6)alkyl)2N-, or (C1-C6)alkyl(H)C=NO-, or ((C1-C6)alkyl)2C=NO-. All hydrolyzable silyl groups of the (A)HSG-FP copolymer may be the same. The hydrolyzable silyl groups are derived from the hydrolyzable silyl groups of at least one alkenyl-functional hydrolyzable silane (comonomer) from which the comonomer units of the (A)HSG-FP copolymer containing such groups are generated.

[0015] Aspect 6. The moisture-curable polyethylene composition of any one of aspects 1 to 5, wherein the (B) condensation cure catalyst is selected from any one of (i) to (iv), i.e., (i) a Bronsted acid, (ii) a Bronsted base, (iii) a Lewis acid, and (iv) a Lewis base. (B) can be either (i) or (iii), or alternatively either (ii) or (iv). (B) can be a Lewis acid, which can be a dialkyltin dicarboxylate. (B) can be a Bronsted acid, which can be a sulfonic acid of formula RSO3H, where R is (C1-C 10 )Alkyl, (C6-C 10 )Aryl, (C1-C 10 ) Alkyl-substituted (C6-C 10 ) aryl, or (C6-C 10 )Aryl-substituted (C1-C 10 ) alkyl, or blocked sulfonic acids, which allow the sulfonic acid to be generated in situ.

[0016] Embodiment 7. The moisture-curable polyethylene composition of any one of embodiments 1 to 6, comprising a total of greater than 0 wt. % to 84.99 wt. % of one or more optional additives, the additives being selected from additives (C) to (I), i.e., (C) antioxidants, (D) colorants, (E) moisture scavengers, (F) stabilizers for stabilizing the formulation against the effects of ultraviolet light such as hindered amine light stabilizers (HALS) (UV stabilizers), (G) processing aids, (H) flame retardants, (I) polymers that are not (A), and combinations of any two or more of (C) to (I). For example, the composition may further include any one, or any four, or each of: (C) an antioxidant such as pentaerythritol tetrakis(3-(3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl)propionate; (D) a colorant such as carbon black and / or titanium dioxide; (E) a moisture scavenger such as octyltriethoxysilane; (F) a UV stabilizer such as HALS; and (I) a polymer that is not (A), such as LLDPE.

[0017] The moisture-curable polyethylene composition of any one of Embodiments 1-7 can comprise 50.9 to 99.90 wt.%, alternatively 90.0 to 98 wt.%, of the (A) HSG-FP copolymer, 0.10 to 1.0 wt.%, of the (B) condensation cure catalyst, and a total of 0 to 48.10 wt.%, alternatively 1.0 to 9.0 wt.%, of one or more optional additives (e.g., (C), (D), (E), (F), and / or (I)), all weight percentages based on the total weight of the composition. Alternatively, the formulation of any one of the embodiments 1-7 may include 15.9-38.9 wt% of (A) HSG-FP copolymer, 0.10-1.0 wt% of (B) condensation cure catalyst, 80.0-60.0 wt% of (H) flame retardant, and 1.0-4.0 wt% total of one or more optional additives (e.g., (C), (D), (E), (F), and / or (I)), all weight percentages based on the total weight of the composition. (A) HSG-FP copolymer may be produced by copolymerizing ethylene, one or two alkenyl-functional hydrolyzable silanes, or one alkenyl-functional hydrolyzable silane, and zero, one, two, or more optional comonomers. (A) HSG-FP copolymer may be produced by copolymerizing ethylene, at least one alkenyl-functional hydrolyzable silane (comonomer), and optionally propylene (HC=C(H)CH).

[0018] Aspect 8. A moisture-curable polyethylene composition comprising: (A) a (hydrolyzable silyl group)-functional polyethylene copolymer (HSG-FP copolymer); (B) a condensation cure catalyst; and zero, one, or more optional additives, the composition having characteristics (i)-(iv), i.e., (i) curable under ambient conditions including air, a temperature of 23° C.±2° C., and a relative humidity of 50% RH±2% RH in less than 15 days to produce a cured polymer product characterized by a hot creep percentage of 100% or less (≦); (ii) curable under ambient conditions including air, a temperature of 23° C.±2° C., and a relative humidity of 50% RH±2% RH in less than 23 days to produce a hot creep percentage of 80% or less. (iii) is curable by immersion in hot water at 90° C.±2° C. for 20.0 hours to produce a cured polymer composition characterized by a hot creep percentage of less than 19% when the composition does not contain a polymer that is not (A); or (iv) is curable by immersion in hot water at 90° C.±2° C. for 20.0 hours to produce a cured polymer composition characterized by a hot creep percentage of less than 50% when the composition contains 46% by weight linear low density polyethylene (LLDPE), all as measured by the Hot Creep Test Method described below. The moisture curability of the composition is characterized by any one of the combinations of features (v) through (xii): (v) both (i) and (ii); (vi) both (i) and (iii); (vii) both (i) and (iv); (viii) both (ii) and (iii); and (ix) both (ii) and (iv). (x) both (iii) and (iv); (xi) any three of (i) through (iv); (xii) each of (i) through (iv), all as measured by the hot creep test method described below. Characteristic (i) may be achieved in less than 13 days, alternatively less than 10 days, alternatively less than 8 days, alternatively less than 4 days, alternatively less than 3 days, alternatively less than 2 days, alternatively less than 1 day; Characteristic (ii) may be achieved in less than 20 days, alternatively less than 17 days, alternatively less than 15 days, alternatively less than 13 days, alternatively less than 10 days, alternatively less than 5 days, alternatively less than 4 days, alternatively less than 3 days, alternatively less than 2 days, alternatively less than 1 day.When the composition does not include a non-(A) polymer, characteristic (iii) may be less than 17.5%. When the composition includes 46 wt% LLDPE (e.g., LLDPE (I)-1, described below), characteristic (iv) may be less than 30%. The composition may be the moisture-curable polyethylene composition of any one of embodiments 1 to 7. The number of days to achieve 100% hot creep, following characteristic (i), may be at least 0.6 days, alternatively at least 1.0 days, alternatively at least 2 days. The number of days to achieve 80% hot creep, following characteristic (ii), may be at least 0.8 days, alternatively at least 2 days, alternatively at least 3 days. The hot creep percentage of characteristic (iii) may be at least 7%, alternatively at least 7.6%. The hot creep percentage of characteristic (iv) may be at least 20%, alternatively at least 22%.

[0019] Embodiment 9. A method of producing a cured polymer product, the method comprising moisture curing the moisture curable polyethylene composition of embodiment 8 to obtain a cured polymer product, the moisture curing being characterized by any one of features (i) to (xii), except that "curable" is replaced with "cured", i.e., the curing is performed according to the conditions of any of features (i) to (xii).

[0020] Embodiment 10. A method of producing a moisture-curable polyethylene composition according to any one of embodiments 1 to 8, the method comprising: mixing a melt of (A) a (hydrolyzable silyl group) functional polyethylene copolymer and (B) a condensation cure catalyst to obtain a melt mixture comprising a melt of (A) and (B) the condensation cure catalyst; and extruding the melt mixture to produce the moisture-curable polyethylene composition. The method may further comprise adding at least one of additives (C) through (I) to the melt of (A) or to the melt mixture of (A) and (B) to produce the composition of embodiment 7.

[0021] Embodiment 11. A cured polymer product produced by moisture curing the moisture curable polyethylene composition of any one of embodiments 1-8 to obtain a cured polymer product. The composition may be moisture cured in its solid or molten state. Moisture curing may be carried out under ambient conditions including an air atmosphere, an ambient temperature (e.g., 20 to 40 degrees Celsius (°C)), and an ambient relative humidity (e.g., 10 to 90 percent relative humidity (%RH)). Alternatively, moisture curing may be carried out under greater than ambient conditions including an air atmosphere, a temperature between 41 degrees Celsius (°C) and 95°C, and a relative humidity between 10.0 percent (%RH) and 100%RH. The cured polymer product may be an insulating or semiconducting layer or an outer shield layer of a coated conductor, as described below.

[0022] Embodiment 12. A product comprising the moisture-curable polyolefin composition of any one of embodiments 1-8, or the cured polymer product of embodiment 11. Examples include a coating on a substrate, a tape, a film, a layer of a laminate, a foam, or a pipe.

[0023] A coated conductor comprising a conductive core and a polymer layer at least partially surrounding the conductive core, at least a portion of the polymer layer comprising the cured polymer product of Aspect 11. The entire polymer layer may comprise the cured polymer composition. The conductive core may be linear (e.g., wire-like) having a length and proximal and distal ends spaced apart from each other by the length of the linear shape, and the polymer layer may surround the conductive core except for the proximal and distal ends. The coated conductor may further comprise one or more additional polymer layers, which may or may not independently comprise the cured polymer composition, and / or an outer shield layer (e.g., a metal sheath or sleeve). The coated conductor may comprise one or two insulating layers, at least one of which comprises a cured polymer composition, and alternatively or additionally, one or two semiconducting layers, at least one of which comprises a cured polymer composition including carbon black, and alternatively or additionally, an outer shield layer comprising a cured polymer composition.

[0024] Embodiment 14. A method of conducting electricity comprising applying a voltage across the conductive core of the coated conductor of embodiment 13 to generate a flow of electricity through the conductive core. The conductive core can have a length and proximal and distal ends spaced apart by the length, and electricity can flow the length of the conductive core from the proximal end to the distal end or vice versa.

[0025] Also, the moisture-curable polyethylene composition may be moisture cured at temperatures below the melting temperature of 41°C to (A) (e.g., below 115°C), in a non-air (e.g., nitrogen gas) atmosphere having a relative humidity of 10% to 100% RH, or both. All other conditions being equal, the higher the temperature and / or the higher the % RH, the faster the composition will moisture cure and / or the greater the degree of crosslinking in the cured product.

[0026] Advantageously, the moisture curable polyethylene composition can be rapidly moisture cured under typical ambient conditions, including air, a temperature of 23° C., and a relative humidity of 50% RH, to produce a cured polymer product characterized by a hot creep percentage of 100% or less in less than 15 days, alternatively less than 13 days, alternatively less than 10 days, alternatively less than 8 days, alternatively less than 4 days, alternatively less than 3 days, alternatively less than 2 days, alternatively less than 1 day, all as measured by the Hot Creep Test Method described below. For use of the cured polymer composition as an insulating or semiconducting layer in a power cable, such as a low voltage (LV) power cable, a high temperature creep of less than 175% is desirable. Power cables may experience operating temperatures higher than ambient temperatures, and at elevated temperatures, it is desired that the power cable not sag or droop significantly. All other conditions being equal, the lower the hot creep percentage, the better the power cable will perform. The compositions can be moisture cured under these representative ambient conditions to produce cured polymer compositions characterized by a hot creep percentage of less than 80% in less than 23 days, alternatively less than 20 days, alternatively less than 17 days, alternatively less than 15 days, alternatively less than 13 days, alternatively less than 10 days, alternatively less than 5 days, alternatively less than 4 days, alternatively less than 3 days, alternatively less than 2 days, alternatively less than 1 day, all as measured by the Hot Creep Test Method described below. To determine the number of days required to achieve 100% or 80% hot creep, the hot creep percentage of test materials subjected to curing under ambient conditions is measured periodically for 1 to 182 days, alternatively 1 to 70 days, alternatively 1 to 35 days. For example, the hot creep percentage can be measured after ambient curing for 1 day, 2 days, 3 days, 4 days, 7 days, 10 days, 14 days, 21 days, 28 days, and 35 days. The measured hot creep percentage values ​​are then plotted as the y-axis values ​​versus time (in days) as the x-axis values. Plot the data as a line graph or best fit a straight line to the data. Read off the line (or interpolate) the number of days to achieve 100% and 80% hot creep.

[0027] The moisture curable polyethylene composition can be moisture cured by immersion in hot water at 70°C to 95°C for less than 24 hours to produce a cured polymer composition having a final (maximum) degree of crosslinking. The final degree of crosslinking of the cured polymer composition can be characterized by immersing the composition in a 90°C water bath for 20 hours to obtain a cured polymer composition having a final degree of crosslinking, measured as a hot creep percentage. The hot creep percentage of the cured polymer product can be less than 19%, or less than 17.5% if the composition does not include a (I) polymer that is not (A) (e.g., does not include an LLDPE resin). If the composition includes 46 wt% LLDPE, the hot creep percentage of the cured polymer product can be less than 50%, alternatively less than 30%, alternatively less than 25%.

[0028] To compare hot creep percentage results of different samples of the same moisture-curable polyethylene composition or different compositions, those moisture-curable polymer compositions can be configured for hot creep measurement by extruding the cured product as a tape having a thickness of 1.370 millimeters (mm, 54 mil) to 1.60 mm (63 mil), and the hot creep performance (%) of the tape can be measured at 0.2 megapascals (MPa) and 200° C. All other conditions being equal, the thicker the tape, the longer it will take to achieve a particular hot creep percentage value.

[0029] The total weight of all components, including additives, in the moisture-curable polyethylene composition is 100.00% by weight. All other things being equal, the higher the loading (amount) of (A) HSG-FP copolymer in the composition, the faster the moisture cure will occur under ambient conditions. All other things being equal, the higher the loading (amount) of (B) condensation cure catalyst in the composition, the faster the moisture cure will occur under ambient conditions.

[0030] The moisture-curable polyethylene composition may consist essentially of the necessary components (A) and (B) above. The term "consist essentially of" means that these embodiments of the composition may not include an added component selected from any one of components (i) to (vii), i.e. (i) a blowing agent or blowing agent, such as azodicarbonamide; (ii) a (hydrolyzable silyl group)-functional polyethylene copolymer that is not (A); (iii) a polyethylene polymer that is not a reactor polyethylene; (iv) an ethylene / ethyl acrylate (EEA) copolymer or other acrylate-containing polymer; (v) a metal carboxylate, where the metal is any metal other than tin; (vi) any four of (i) to (v); (vii) each of (i) to (v). "Additive component" means a component that is intentionally introduced. Some of the components (i)-(v) are present as impurities during the synthesis of (e.g., carried over from the synthesis of (A) HSG-FP copolymer or the synthesis of any of the aforementioned components (e.g., additive (C) to (I)), or are carried over from thereto, and are thereby unintentionally introduced into the composition. If these impurities are present, they are not expected to be at levels that have a measurable beneficial or detrimental effect on the performance of the composition. If the composition does not include any of the components (i)-(vii), the moisture cured polymer product, products, and coated conductors produced therefrom, as well as the methods of producing or using them, may also not include any of the same components (i)-(vii). Alternatively, the composition may consist essentially of at least one of the optional additives (C)-(I) of its components (A) and (B) as described above.

[0031] The moisture-curable polyethylene composition can be produced according to the methods described above or illustrated in the Examples below. The composition can be produced in continuous (monolithic) or divided solid form. The composition can be extruded, pelletized, and / or molded to provide the composition as a solid (e.g., molded or pelleted).

[0032] The moisture-curable polyethylene composition may be produced as a one-part composition or a multiple-part composition, e.g., a two-part composition. The two-part composition may comprise a first and a second part, the first part consisting essentially of the (hydrolyzable silyl group) functional polyethylene copolymer and optionally any one or more additives (C)-(I), and the second part consisting essentially of the (B) condensation cure catalyst or catalyst masterbatch comprising a carrier resin (as an example of an (I) polymer that is not (A)) and (B), and an optional additional portion of A) HSG-FP copolymer, and optionally one or more additives (C)-(I).

[0033] The moisture-curable polyethylene composition may be free of water (anhydrous) or may further comprise water.

[0034] (A) (Hydrolyzable Silyl Group)-Functional Polyethylene Copolymers ("HSG-FP Copolymers"). Polymers, or aggregates thereof, i.e., reactor copolymers of ethylene (monomer) and at least one alkenyl-functional hydrolyzable silane comonomer. (A) HSG-FP Copolymers are at least 70% by weight, alternatively at least 73% by weight, alternatively at least 83% by weight, alternatively at least 93% by weight, of ethylene constituent units, 0.38 to 0.99 mol % of hydrolyzable silyl group-containing comonomer units derived from at least one alkenyl-unsaturated hydrolyzable silane, 0 to 2% by weight of propylene constituent units (if present) derived from propylene, and / or (C4-C 20 0-20% by weight of (C4-C 20 ) alpha-olefin building blocks. Along the backbone of (A), the different types of building blocks are randomly intermingled with each other. The backbone of (A) HSG-FP copolymer is structurally distinct from the homogeneous backbone of HSG grafted polyethylene homopolymer or the segmented backbone of polyorganosiloxane-polyethylene block copolymer. (A) may not contain hydrolyzable silyl groups grafted in the post-HPT reactor process.

[0035] All other conditions being equal, the higher the temperature and / or pressure of the HPT reactor used in the production process of (A) HSG-FP copolymer, the higher the molecular weight dispersity of (A). All other conditions being equal, the absolute molecular weight ratio (M z(abs) / M w(abs) The higher the dispersity ratio ((M z(abs) / M w(abs) ) / (M w(conv) / M n(conv) The higher the hydrolyzable silyl group content of the (A) HSG-FP copolymer, the faster and / or greater the cure of the composition. As a result, if desired, the composition can be readily moisture cured under ambient conditions, including 23° C. and 50% RH. All other conditions being equal, the higher the hydrolyzable silyl group content of the (A) HSG-FP copolymer, the faster and / or greater the cure of the moisture-curable polyethylene composition.

[0036] The (A)HSG-FP copolymers do not contain metal-containing olefin polymerization catalysts and therefore do not contain by-products derived from such catalysts, such as residual catalyst metal content and / or residual catalyst ligands. Examples of excluded metal-containing olefin polymerization catalysts are chromium and chromium oxide catalysts, metallocene catalysts, post-metallocene catalysts, and Ziegler-Natta catalysts. Thus, the (A)HSG-FP copolymers do not contain metals selected from chromium, titanium, zirconium, and hafnium, and do not contain organic ligands used in metallocene or post-metallocene catalysts.

[0037] (A) HSG-FP copolymers are copolymers, meaning that (A) comprises polyethylene molecules containing covalently attached condensation curable silicon-containing groups that can be further polymerized via a water-based condensation cure to form covalent siloxysilyl crosslinks between different chains of the polyethylene molecules, thereby providing multiple structural units in at least one type of chain of the resulting moisture-cured polymer product that contain siloxysilyl crosslinks (Si-O-Si) attached to carbon atoms of different chains.

[0038] (A) HSG-FP copolymers are produced in the HPT reactor using an organic peroxide to initiate and continue the copolymerization. The organic peroxide can be an organic hydrogen peroxide such as tert-butyl hydroperoxide, 1,1-dimethylethyl hydroperoxide, 1,1-dimethylpropyl hydroperoxide, benzoyl hydroperoxide, tert-butyl hydroperoxide, tert-amyl hydroperoxide, or cumyl hydroperoxide. Alternatively, the organic peroxide may be bis(1,1-dimethylethyl)peroxide, bis(1,1-dimethylpropyl)peroxide, 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexane, 2,5-dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexyne, 4,4-bis(1,1-dimethylethylperoxy)valeric acid, butyl ester, 1,1-bis(1,1-dimethylethylperoxy)-3,3,5-trimethylcyclohexane, benzoyl peroxide, tert-butyl peroxybenzoate, di-tert-amyl peroxide ("DTAP"), bis(alpha-t-butyl The peroxide may be a diorganohydrogen peroxide such as 4,4-di(tert-butylperoxy)butyl valerate, di(isopropylcumyl)peroxide, or dicumyl peroxide.

[0039] (A) At least one alkenyl-functional hydrolyzable silane used to produce the HSG-FP copolymer has the formula (III): 2 ) m (R 3 ) 3-m Si-Q q -(C2-C6)alkenyl (III), 2 , and R 3is as defined above for formula (II), the subscript q is 0 or 1, and the divalent group Q is (C1-C6)alkylene-C(=O)- or (C1-C6)alkylene-OC(=O)-. (C2-C6)alkenyl can be vinyl, allyl, 3-butenyl, or 5-hexenyl. Each (C1-C6)alkylene can be linear or branched. Examples of (C1-C6)alkylene are (C4-C6)alkylene, (C1-C3)alkylene, CH2, CH2CH2, CH2CH2CH2, and CH2C(CH3)2-. (A) The HSG-FP copolymer can be a reactor copolymer of ethylene and at least one, or up to two, or one of vinyltrimethoxysilane, (acryloxypropyl)trimethoxysilane, (methacryloxypropyl)trimethoxysilane, vinyltri(2-propanoneoximo)silane, or vinyl(tris(diethylamino)silane. Vinyltrimethoxysilane is an example of an alkenyl-functional hydrolyzable silane of formula (III), where subscript m is 3, subscript q is 0, and each R 2 is (C1-C6)alkoxy (i.e., methoxy) and (C2-C6)alkenyl is vinyl (-C(H)=CH2). The comonomer units of the (A) HSG-FP copolymer derived from at least one alkenyl-functional hydrolyzable silane are referred to herein as alkylene hydrolyzable silyl group units because the alkenyl group of the at least one alkenyl-functional hydrolyzable silane reacts during copolymerization to form a divalent alkylene linking group that covalently bonds the hydrolyzable silyl groups of the HSG-FP copolymer.

[0040] The (A)HSG-FP copolymers may have a crystallinity of 45.0 wt% or less, alternatively 5-44.4 wt%, alternatively 15-44.4 wt%, alternatively 25-44.4 wt%, alternatively less than 44.5 wt%, alternatively 35-44.4 wt%, alternatively 42.0-44.1 wt% when measured at room temperature (23°C) according to the Crystallinity Test Method described below. Compared to HSG-FP copolymers having a crystallinity of greater than 45 wt% at room temperature (23°C), these embodiments of the (A)HSG-FP copolymers may beneficially provide faster moisture cure and / or improved filler acceptance (ability to accept higher filler loadings) at ambient or room temperature conditions.

[0041] The (A) HSG-FP copolymer may be present in the moisture curable polyethylene composition at 25.0 to 99.99 wt%, alternatively 25.0 to 99.90 wt%, alternatively 45 to 99.99 wt%, alternatively 45 to 99.90 wt%, alternatively 50.9 to 99.90 wt%, alternatively 65.0 to 99.90 wt%, alternatively 88 to 97 wt%, alternatively 89.0 to 95.0 wt%, provided that when (B) is a dialkyltin dicarboxylate, (A) is up to 99.90 wt% of the composition, all based on the total weight of the composition, and when (B) is a sulfonic acid or blocked sulfonic acid, (A) is 25 to 99.99 wt% of the composition, or any one of the (A) subranges set forth above.

[0042] (B) Condensation cure catalyst. (B) Condensation cure catalyst may be referred to as a silanol condensation catalyst. However, (B) condensation cure catalyst is not limited to catalyzing the condensation cure of silanol groups themselves. (B) may be, for example, a silanol group represented by the formula (R 2 ) m (R 3 ) 3-m Si-Q q -(C2-C6) alkyl monovalent radicals, 2 and R 3 and the divalent group Q is as defined above. (R 2 ) m (R3 ) 3-m Examples of Si- are alkoxysilyl, oximinosilyl, dialkylaminosilyl, and alkylaminosilyl groups. (B) can be any acid that can lower the pH of pH 7.00 water to a pH < 6.00, or a base that can raise the pH of pH 7.00 water to a pH > 8.00.

[0043] (B) The condensation cure catalyst may include a dialkyltin dicarboxylate. The dialkyltin dicarboxylate may be a di((C1-C 10 ) alkyl) tin dicarboxylate, or dialkyltin di(C8-C 18 ) carboxylate, or di((C1-C 10 ) alkyl) tin(C8-C 18 ) carboxylate, or di((C3-C5) alkyl)tin di(C 10 -C 14 ) carboxylate, or di((C4) alkyl)tin di(C 12 ) carboxylate, or dibutyltin dilaurate (DBTDL). If a dialkyltin dicarboxylate is the only (B) in the composition, it is present therein at 0.10 wt. % or more, alternatively 0.12 wt. % or more.

[0044] (B) The condensation cure catalyst may include a sulfonic acid. The sulfonic acid may be a sulfonic acid of formula RSO3H, where R is (C1-C 10 )Alkyl, (C6-C 10 )Aryl, (C1-C 10 ) Alkyl-substituted (C6-C 10 ) aryl, or (C6-C 10 )Aryl-substituted (C1-C 10) alkyl. The sulfonic acid can be a hydrophobic sulfonic acid, having a solubility in pH 7.0 distilled water of less than 0-0.1 g / mL after 24 hours at 23°C. The sulfonic acid can be methanesulfonic acid, benzenesulfonic acid, alkylbenzenesulfonic acid (e.g., 4-methylbenzenesulfonic acid, dodecylbenzenesulfonic acid, or dialkylbenzenesulfonic acid), naphthalenesulfonic acid, or alkylnaphthalenesulfonic acid. (C6-C 10 The arylsulfonic acid may be benzenesulfonic acid or naphthalenesulfonic acid. The sulfonic acid may be composed of carbon atoms, hydrogen atoms, one sulfur atom, and three oxygen atoms.

[0045] (B) The condensation curing catalyst may include a blocked sulfonic acid. The blocked sulfonic acid may be as defined in US Patent Application Publication No. 2016 / 0251535A1 and may be a compound that generates a sulfonic acid of formula RSO3H in situ, where R is as defined above when it is heated, optionally in the presence of moisture or alcohol. Examples of blocked sulfonic acids include amine-sulfonate salts and sulfonic acid alkyl esters. The blocked sulfonic acid may consist of a carbon atom, a hydrogen atom, one sulfur atom, and three oxygen atoms, and optionally a nitrogen atom.

[0046] (B) The condensation cure catalyst may include a combination of a dialkyltin dicarboxylate and a sulfonic acid. The dialkyltin dicarboxylate may be dibutyltin dilaurate, and the sulfonic acid may be an aryl sulfonic acid or an alkyl-substituted aryl sulfonic acid. The aryl sulfonic acid may be benzene sulfonic acid or naphthalene sulfonic acid.

[0047] (B) the condensation cure catalyst may be present in the moisture curable polyethylene composition at 0.01 to 5 wt%, alternatively 0.010 to 5.0 wt%, alternatively 0.05 to 5.0 wt%, alternatively 0.10 to 5.0 wt%, alternatively 0.11 to 0.50 wt%, alternatively 0.50 to 1.0 wt%, alternatively 1.0 to 4.0 wt%, provided that when (B) is only a dialkyltin dicarboxylate, the dialkyltin dicarboxylate is at least 0.10 wt%, alternatively at least 0.11 wt%, and (A) is up to 99.90 wt%, alternatively up to 99.89 wt%. When (B) is a sulfonic acid or blocked sulfonic acid, the sulfonic acid or blocked sulfonic acid is 0.01 to 5 wt% of the composition, or any one of the subranges of (B) above.

[0048] Optional Additive (C) Antioxidant: An organic molecule, or collection of such molecules, that inhibits oxidation. The (C) antioxidant is compositionally distinct from the (F) stabilizer, i.e., when a composition contains both (C) and (F), the compound used as (C) is distinct from the compound used as (F). The (C) antioxidant functions to provide antioxidant properties to the moisture curable polyethylene composition and / or the cured polymer product.Examples of suitable (C) are bis(4-(1-methyl-1-phenylethyl)phenyl)amine (e.g. NAUGARD 445), 2,2'-methylene-bis(4-methyl-6-t-butylphenol) (e.g. VANOX MBPC), 2,2'-thiobis(2-t-butyl-5-methylphenol) (CAS number 90-66-4, 4,4'-thiobis(2-t-butyl-5-methylphenol) (also known as 4,4'-thiobis(6-tert-butyl-m-cresol), CAS number 96-69-5, commercially available LOWINOX TBM-6), 2,2'-thiobis(6-t-butyl-4-methylphenol) (CAS number 90-66-4, commercially available LOWINOX TBM-6), TBP-6), tris[(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)methyl]-1,3,5-triazine-2,4,6-trione (e.g., CYANOX 1790), pentaerythritol tetrakis(3-(3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl)propionate) (e.g., IRGANOX 1010, CAS number 6683-19-8), 3,5-bis(1,1-dimethylethyl)-4-hydroxybenzenepropanoic acid 2,2′-thiodiethanediyl ester (e.g., IRGANOX 1035, CAS number 41484-35-9), distearyl thiodipropionate ("DSTDP"), dilauryl thiodipropionate (e.g., IRGANOX 1035, CAS number 41484-35-9), PS800), stearyl 3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate (e.g., IRGANOX 1076), 2,4-bis(dodecylthiomethyl)-6-methylphenyl (IRGANOX 1726), 4,6-bis(octylthiomethyl)-o-cresol (e.g., IRGANOX 1520), and 2′,3-bis[[3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionyl]]propionohydrazide (IRGANOX 1024).(C) is 4,4′-thiobis(2-t-butyl-5-methylphenol) (also known as 4,4′-thiobis(6-tert-butyl-m-cresol)), 2,2′-thiobis(6-t-butyl-4-methylphenol, tris[(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)methyl]-1,3,5-triazine-2,4,6-trione, distearyl thiodipropionate, or dilauryl thiodipropionate, or any two or more thereof. The combination may be tris[(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)methyl]-1,3,5-triazine-2,4,6-trione and distearyl thiodipropionate. The composition and / or cured polymer product may be free of (C). The (C) antioxidant, if present, may be 0.01 to 1.5 wt. %, alternatively 0.1 to 1.0 wt. %, of the total weight of the moisture-curable polyolefin composition and / or product.

[0049] Optional Additive (D) Colorant. For example, a pigment or dye. For example, carbon black or titanium dioxide. Carbon black may be provided as a carbon black masterbatch, which is a composition of poly(1-butene-co-ethylene) copolymer (95% to less than 100% by weight of the total weight of the masterbatch) and carbon black (0% to less than 5% by weight of the total weight of the masterbatch). Carbon black is a microcrystallized form of quasicrystalline carbon and has a high surface area to volume ratio, but less than that of activated carbon. Examples of carbon black are furnace carbon black, acetylene carbon black, conductive carbon (e.g., carbon fiber, carbon nanotubes, graphene, graphite, and expanded graphite platelets). The moisture-curable polyethylene composition and / or the cured polymer product may be free of (D). If present, (D) is 0.1 to 35% by weight of the formulation, alternatively 1 to 10% by weight.

[0050] (E) Moisture Scavenger as an Optional Additive. (E) Moisture Scavenger functions to inhibit premature moisture cure of the moisture curable polyethylene composition, which may result from premature or prolonged exposure of the composition to ambient air or when the composition is at ambient or elevated temperatures (e.g., during melt extrusion). Examples of (E) are hexadecyltrimethoxysilane, octyltriethoxysilane, and octyltrimethoxysilane. The composition and / or the cured polymer product may be free of (E). (E), when present, may be 0.001 to 5.0 wt. %, alternatively 0.01 to 3.0 wt. %, alternatively 0.10 to 1.5 wt. %, alternatively 0.15 to 1.0 wt. % of the dielectric reinforced polyethylene composition.

[0051] Optional additive (F) a stabilizer for stabilizing the moisture-curable polyethylene composition against ultraviolet light (UV stabilizer). (F) stabilizer is compositionally distinct from (C) antioxidant, meaning that if a formulation contains both (C) and (F), the compound used as (C) is distinct from the compound used as (F). Examples include hindered amine light stabilizers (HALS), benzophenones, or benzotriazoles. (F) can be a molecule, or an aggregate of such molecules, containing a basic nitrogen atom bonded to at least one sterically bulky organic group and functioning as an inhibitor of degradation or decomposition. HALS are compounds that have sterically hindered amino functional groups and can inhibit oxidative degradation and also increase the shelf life of embodiments of compositions containing organic peroxides. Examples of suitable (F) are butanedioic acid dimethyl ester, polymers containing 4-hydroxy-2,2,6,6-tetramethyl-1-piperidine-ethanol (CAS number 65447-77-0, commercially available LOWILITE62), and N,N'-bisformyl-N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-hexamethylenediamine (CAS number 124172-53-8, commercially available Uvinul 4050 H). The compositions and products may be free of (F). When present, the (F) UV stabilizer may be 0.001 to 1.5% by weight of the composition, alternatively 0.002 to 1.0% by weight, alternatively 0.05 to 0.1% by weight.

[0052] (G) Processing aids as optional additives: Molecules that reduce adhesion of the polymer melt in manufacturing equipment such as extruders and dies and reduce melt fracture of materials. (G) can be fluoropolymers, polyorganosiloxanes, metal salts of fatty carboxylic acids, fatty carboxamides, waxes, ethylene oxide (co)polymers, and non-ionic surfactants. Formulations and products may be free of (G). When present, (G) processing aids may be 0.05-5% by weight of the composition.

[0053] (H) Flame Retardants as Optional Additives. (H) Flame retardants are compounds that inhibit or slow the spread of fire by inhibiting chemical reactions in a flame. (H) Flame retardants can be (H1) minerals, (H2) organic halogen compounds, (H3) (organic) phosphorus compounds, (H4) halogenated silicones, (H5) a combination of any two or more of (H1)-(H4), or (H6) a combination of any one of (H1)-(H4) with a flame retardant synergist (e.g., antimony trioxide). The compositions and products may be free of (H). When present, (H) flame retardants can be 0.1-80.0 wt.%, alternatively 1-50.0 wt.%, alternatively 5-30.0 wt.% of the composition.

[0054] The moisture curable polyethylene composition may further comprise a (I) polymer that is not (A) or a styrenic polymer (not (A)). The (I) polymer that is not (A) may be a polyolefin-based polymer that is compositionally different from the (A) HSG-FP copolymer. The (I) polymer that is not (A) may be a polyolefin, a styrenic polymer, a rubber, or a blend of any two or more thereof. The (I) polymer that is not (A) may be a polyolefin that is an ethylene-based polymer, a propylene-based polymer, a poly(C4-C8) alpha-olefin-based polymer, a polydiene, or any blend of two or more thereof. The ethylene-based polymer may be a linear low density polyethylene (LLDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), high density polyethylene (HDPE) homopolymer produced by coordination polymerization, low density polyethylene (LDPE) homopolymer produced by radical polymerization, ethylene / propylene copolymer, ethylene / 1-butene copolymer, ethylene / 1-hexene copolymer; ethylene / 1-octene copolymer, ethylene / diene copolymer, ethylene / propylene / alpha-olefin copolymer, ethylene / propylene / diene (EPDM) copolymer, ethylene / vinyl acetate (EVA) copolymer, ethylene / alkyl (meth)acrylate (EAA) copolymer, acrylate-terminated oligomer or polymer not containing silicon atoms (not an EAA polymer), or ethylene / maleic anhydride copolymer. (I) may be a styrene-based polymer. Or (I) may be natural rubber, nitrile rubber, chlorosulfonated polyethylene (CSM), chlorinated polyethyl (CPE), neoprene rubber, or butyl rubber. Or (I) can be a vinyl terminated organosiloxane oligomer, or an allyl terminated organosiloxane oligomer. (I) can be LLDPE, LDPE, MDPE, HDPE, an EVA copolymer, or an EEA copolymer, or LLDPE, LDPE, MDPE, or HDPE, or LLDPE, or an EVA or EEA copolymer.

[0055] The (I) polymer that is not (A) may be a homopolymer of ethylene having a carbon atom backbone with hydrolyzable silyl groups grafted thereto, such as a polymer produced by a process (e.g., the SIOPLAS™ process) that typically involves reacting and grafting a hydrolyzable unsaturated silane (e.g., vinyltrimethoxysilane) during post-polymerization compounding or extrusion promoted by a free radical initiator such as a dialkyl peroxide, and isolating the resulting silane-grafted polymer. The grafted polymer may be for use in a later processing step. The MONOSIL™ process is described, for example, in US 3,646,155 and WO 2019 / 005439 A1.

[0056] The (I) polymer, which is not (A), may be used in the moisture-curable polyethylene composition in neat form (i.e., without the (B) condensation cure catalyst and any additives such as additives (C) to (H)). Alternatively, the (I) polymer, which is not (A), may be used in the composition in masterbatch form with (I) as the carrier resin and at least one additive selected from (B) condensation cure catalyst and any additives such as additives (C) to (H). A masterbatch with (I) and (B) as the carrier resin is a catalyst masterbatch. A masterbatch with (I), (B), and any one or more of (C) to (H) as the carrier resin is an additive masterbatch. A masterbatch with (I), (B), and any one or more of (C) to (H) as the carrier resin is a masterbatch that combines catalyst and additive. Catalyst masterbatches and additive masterbatches may be commercially available.

[0057] The amount of the (I) polymer that is not (A) in the moisture curable polyethylene composition can be 0 weight percent when the (I) polymer that is not (A) is not present, or from greater than 0 to 85 weight percent when the (I) polymer that is not (A) is present. When present, the amount of the (I) polymer that is not (A) can be from greater than 0 to 10 weight percent, alternatively from greater than 10 to 50 weight percent, alternatively from 51 to 85 weight percent, alternatively from 41 to 49 weight percent.

[0058] The moisture curable polyethylene composition may include one or more other additives as optional additives, such as organic peroxides (e.g., dicumyl peroxide or tert-butyl peroxyacetate), scorch inhibitors (e.g., 2,4-diphenyl-4-methyl-1-pentene (also known as α-methylstyrene dimer or AMSD), tree retarders (water or electrical tree retarders, e.g., polyethylene glycol), moisture generators (e.g., calcium oxalate monohydrate, for in situ water generation), hydroxyl functional organosiloxanes (e.g., hydroxyl terminated polydimethylsiloxanes), lubricants, mineral oils, antiblocking agents, metal deactivators (e.g., oxalyl bis(benzylidene)hydrazide (OABH)), coagents, nucleating agents, or combinations of any two or more thereof.

[0059] The moisture-curable polyethylene composition may further comprise 0.01-4.5 wt.% of an organic peroxide, which is added to the (A) HSG-FP copolymer after it is produced. The composition may be further cured by free radical curing, and the cured polymer product may further comprise crosslinking groups that do not include Si atoms. This aspect allows for the dual cure mechanism to provide an embodiment of a cured polymer product that is the product of moisture curing and free radical curing of the composition. The moisture cure may form crosslinks between the hydrolyzable silane groups of (A), the crosslinks having a C-Si-O-Si-C bond motif. The free radical cure enabled by the organic peroxide may form carbon-carbon bond crosslinks between the polymer chains of (A). Thus, the dual cure product may have a different crosslink structure than the moisture cure only product, and therefore different mechanical properties (e.g., modulus, hot creep performance) than the moisture cure only product.

[0060] The (A) HSG-FP copolymer and / or the (I) polymer that is not (A) is (C4-C 20 ) alpha-olefin derived comonomer units. (C4-C 20The alpha-olefin may be a compound of formula (1): H2C=C(H)CH2R, where R is a straight chain (C1-C 18 ) alkyl group. (C1-C 18 ) alkyl groups are monovalent unsubstituted saturated hydrocarbons having 1 to 18 carbon atoms. Examples of R are methyl, ethyl, propyl, butyl, pentyl, hexyl, heptyl, octyl, nonyl, decyl, undecyl, dodecyl, tridecyl, tetradecyl, pentadecyl, hexadecyl, heptadecyl, and octadecyl. In some embodiments, (C3-C 20 ) The alpha-olefins are 1-propene, 1-butene, 1-hexene, or 1-octene, or 1-butene, 1-hexene, or 1-octene, or 1-butene or 1-hexene, or 1-butene or 1-octene, or 1-hexene or 1-octene, or 1-butene, or 1-hexene, or 1-octene, or a combination of any two of 1-butene, 1-hexene, and 1-octene. Alternatively, the alpha-olefins may have a cyclic structure such as cyclohexane or cyclopentane, resulting in alpha-olefins such as 3-cyclohexyl-1-propene (allylcyclohexane) and vinylcyclohexane. (C4-C 20 ) The alpha-olefin may be a (C4-C8) alpha-olefin, or 1-butene, 1-hexene, 1-octene, or a combination of any two thereof, or 1-butene, or 1-hexene, or 1-octene, or a combination of any two thereof.

[0061] The combination of optional additives can be any two, or any five, or each of (C), (D), (E), (F), (H), and (I), which are in addition to and distinct from components (A) and (B).

[0062] The optional additives may be useful to impart at least one property or characteristic to an embodiment in need thereof, including a formulation, product, or method. The property or characteristic may improve the performance of the embodiment, such as when the embodiment is exposed to high temperatures, such as in operations or applications involving melt mixing, extrusion, molding, hot water, and insulation (power cables).

[0063] For clarity, Lewis acids and Bronsted acids are defined herein to be mutually exclusive, and Lewis and Bronsted bases are defined herein to be mutually exclusive (non-overlapping).

[0064] Bronsted acid. A molecular entity that can donate a hydron (proton) to a base (i.e., a hydron donor) or a corresponding chemical species, provided that the molecular entity

[0065] or the corresponding chemical species, provided that they are characterized by a logarithm (pKa) of the acid dissociation constant (log) of less than 6.0. Examples: molecular entities CH3CO2H, H2SO4, HSO4 - , HCl, CH3SO3H and the chemical species H3O + Not H2O, CH3OH, or NH3.

[0066] Bronsted base. A molecular entity that can accept a hydron (proton) from an acid (i.e., a hydron acceptor) or a corresponding chemical species, where the conjugate acid derivative of the molecular entity or corresponding chemical species is characterized by a pKa greater than 8.00. Examples: the molecular entities NH3, amines (pyridine; 1°, 2°, and 3° alkyl and / or aryl amines), and OH - SO4 2- , Cl - , CH3CO2 - , or CH3SO3 - isn't it.

[0067] Lewis acids that are not Brønsted acids. Molecular entities or corresponding chemical species that are electron pair acceptors and therefore can react with Lewis bases to form Lewis adducts by sharing the electron pair donated by the Lewis base. Examples: dialkyltin dicarboxylates, dialkyltin hydroxymonocarboxylates, dialkyltin maleates, tin carboxylates, lead or cobalt naphthenates, and zinc caprylate.

[0068] Lewis base that is not a Brønsted base. A molecular entity or corresponding chemical species that can donate an electron pair and thus coordinate to a Lewis acid, thereby forming a Lewis adduct. Examples are trialkylphosphines and triarylphosphines.

[0069] Monomer-based polymer: a polymer or copolymer having 50.1 to 100% by weight of monomer units and 49.9 to 0% by weight of comonomer units (e.g., an ethylene-based polymer ("ethylenic polymer") having at least 50.1 to 100% by weight of ethylene units and 49.9 to 0% by weight of hydrolyzable silyl group-containing units).

[0070] Olefinically unsaturated. A molecule containing a carbon-carbon double or triple bond or one carbon-carbon double bond.

[0071] Substituted: Any one, all but one, or each functional group can be unsubstituted.

[0072] or precedes different embodiments. "May" is not required but confers the latitude of choice. Optional (optionally): Absent (or excluded) or present (or included).

[0073] Crystallinity Test Method: Determine the melting peak and percent (%) or weight percent (wt%) crystallinity of ethylene-based polymers using a differential scanning calorimeter (DSC) instrument DSC Q1000 (TA Instruments). (A) Baseline calibrated DSC instrument. Use the software calibration wizard. Obtain a baseline by heating the cell from -80°C to 280°C without any sample in the aluminum DSC pan. Then use a sapphire standard as instructed by the calibration wizard. Analyze 1-2 milligrams (mg) of virgin indium sample by heating the standard sample to 180°C, cooling to 120°C at a cooling rate of 10°C / min, then holding the standard sample isothermally at 120°C for 1 minute, followed by heating the standard sample from 120°C to 180°C at a heating rate of 10°C / min. Determine that the indium standard sample has a heat of fusion = 28.71 ± 0.50 Joules per gram (J / g), and onset of melting = 156.6 ± 0.5°C. (B) Conduct DSC measurements on the test sample using a calibrated baseline DSC instrument. Press a test sample of a semi-crystalline ethylene-based polymer into a thin film at a temperature of 160° C. Weigh 5-8 mg of the test sample film into an aluminum DSC pan. Crimp a lid onto the pan to seal the pan and ensure a closed atmosphere. Place the sealed pan into the DSC cell, equilibrate the cell at 30° C., and heat to 190° C. at a rate of approximately 100° C. / min. Hold the sample at 190° C. for 3 minutes and then cool the sample to −60° C. at a rate of 10° C. / min to obtain the cooling curve heat of fusion (H f ) and isothermally held at -60°C for 3 minutes. The sample is then heated again to 190°C at a rate of 10°C / min to obtain the second heating curve heat of fusion (ΔH f) is obtained. The second heating curve is used from -20°C (for ethylene homopolymers, copolymers of ethylene and hydrolyzable silane monomers, and ethylene alpha olefin copolymers with a density equal to or greater than 0.90 g / cm3) or -40°C (for copolymers of ethylene and unsaturated esters, and ethylene alpha olefin copolymers with a density less than 0.90 g / cm3) to the end of melting. The second heating curve is used to calculate the "room temperature" heat of fusion (J / g) from 23°C. The "room temperature" heat of fusion (J / g) is calculated from 23°C (room temperature) to the end of melting. The "total crystallinity" (calculated from the "total" heat of fusion), as well as the "crystallinity at room temperature" (calculated from the "23°C" heat of fusion) are measured and reported. The crystallinity is calculated based on the second heating curve heat of fusion (ΔH f ) and its normalization to the heat of fusion of 100% crystalline polyethylene, where % crystallinity or wt% crystallinity=(ΔHf*100%) / 292 J / g, where ΔH f is as defined above, * indicates mathematical multiplication, / indicates mathematical division, and 292 J / g is the heat of fusion (ΔH f ) is the literature value.

[0074] Density: Measured according to ASTM D792-13, "Standard Test Method for Density and Specific Gravity (Relative Density) of Plastics by Displacement, Method B (for testing solid plastics in liquids other than water, e.g., in liquid 2-propanol)." Units of grams per cubic centimeter (g / cm 3 ).

[0075] Melt Index "I2": Measured in accordance with ASTM D1238-13 using the 190°C / 2.16 kg condition, formerly known as "Condition E". In grams per 10 minutes (g / 10 min).

[0076] A triple detector gel permeation chromatography (3D-GPC or TDGPC) system consisting of PolymerChar (Valencia, Spain) with a 2-angle laser light scattering (LS) detector Model 2040 (Precision Detectors, now Agilent Technologies, California, USA), a 4-capillary solution viscometer (DP) from Polymer Char (Valencia, Spain), and an online solvent degasser from Agilent Technologies is used. Data are collected using PolymerChar's "GPCOne" software. Agilent A high-temperature GPC column consisting of four 30 centimeter (cm) x 20 micrometer (μm) mixed ALS columns from Agilent Technologies is used. The GPC-IR autosampler oven is operated at 160 °C and the column compartment at 150 °C. Test samples are prepared semi-automatically by dosing N2-sparged 1,2,4-trichlorobenzene (TCB) solvent containing 200 ppm of BHT (2,6-di-tert-butyl)-4-methylphenol) from a GPC-IR syringe at a concentration of 2 milligrams (mg) of test sample / milliliter (mL). The test samples are shaken at 160 °C for 3 h. 200 microliters (μL) of sample are injected and eluted at a flow rate of 1.0 milliliters per minute (mL / min) and the elution volume is recorded. Twenty-one narrow molecular weight distribution polystyrene (PS) standards (Polymer Laboratories (now Agilent) Separate at least 10 individual molecular weights and individual concentrations, ranging from 0.25 (peak molecular weight (Mp) >500,000) to 0.5 mg / mL (Mp <500,000), by placing six "cocktail" mixtures of 100000 sachets of 100000 sachets (molecular weights 580 - 8,400,000 g / mol) of 10000 sachets (molecular weights 580 - 8,400,000 g / mol) into a single sachets (molecular weights 580 - 8,400,000 g / mol) and dissolving in TCB at room temperature in the dark for 24 h.

[0077] Polymer Char "GPCOne" software is used to calibrate the column and calculate molecular weights. The following formula is used to convert the peak molecular weight (Mp) of the PS standard to a polyethylene molecular weight: M ポリエチレン =A(M ポリスチレン )B, where calibration point B is 1.0 and calibration point A is 0.38 to 0.44. A column calibration curve is obtained by fitting a first order polynomial to calibration points A and B and the recorded elution volumes. Calibration point A is determined by adjusting the A value of the Williams and Ward equation until a weight average molecular weight Mw calculated using the above equation and a corresponding retention volume polynomial that matches the independently determined Mw value are obtained according to a linear polyethylene homopolymer standard with a known absolute weight average molecular weight of 115,000 g / mol measured by LALLS (low angle laser light scattering) in a manner traceable to standard homopolymer polyethylene NBS 1475.

[0078] Conventional number average molecular weight (M n(conv) ) and conventional weight average molecular weight (M w(conv) ) are calculated according to the following formulas:

number

[0079] Absolute weight average molecular weight (M) was measured by baseline subtracted LS (angle 15 degrees) and IR-5 (measurement signal) concentration detectors. w(abs) ) is calculated using the following formula:

number

number

[0080] Absolute number average molecular weight (M n(abs) ) and absolute z-average molecular weight (M z(abs) ) is calculated using each of the following formulas,

number

[0081] XRF spectroscopy is used to determine the weight percent (wt%) silicon atom (Si) content of the (A) HSG-FP copolymer test sample and then the hydrolyzable silane comonomer unit wt% is calculated. Using a Buehler SimpliMet300 automount press preheated for 3 minutes at 115.6 degrees Celsius (240 degrees Fahrenheit (°F)), the powdered test sample is pressed at 8.3 megapascals (MPa; 1,200 pounds per square inch (psi)) for 1 minute to form a plaque approximately 6 mm thick, and the plaque is allowed to cool to 25 degrees Celsius. PANalytical Analyze the Si atom content of the plaques by wavelength dispersive XRF using an Axios wavelength dispersive X-ray fluorescence analyzer. Determine the Si atom content by comparing the line intensities of the XRF spectrum with a calibration curve of Si atom content established using polymer standards of known Si atom concentration measured individually using either nuclear activation analysis (NAA) or inductively coupled plasma (ICP) techniques. Calculate the hydrolyzable silyl group comonomer unit weight % (i.e., wt %) using the Si atom weight % value measured by XRF and the molecular weight of at least one alkenyl-functional hydrolyzable silane comonomer from which the hydrolyzable silyl group is derived. (A)% of hydrolyzable silyl groups in HSG-FP copolymer. For hydrolyzable silyl groups derived from vinyltrimethoxysilane (VTMS), use a VTMS molecular weight of 148.23 g / mol. To calculate the hydrolyzable silyl group content (wt %) of (A)HSG-FP copolymer, use the Si atom weight % ("C") obtained by XRF and the following formula: p=C*(m / 28.086)(1 / 10000ppmw), where * is multiplication, / is division, p is the weight percent of hydrolyzable silyl groups in (A), C is the Si atomic weight (XFR) in parts per million by weight (ppmw), m is the molecular weight in g / mol of the at least one alkenyl-functional hydrolyzable silane comonomer from which the hydrolyzable silyl groups are derived, 28.086 is the atomic weight of the silicon atom, and 10000ppmw is the number of parts by weight in 1.00% by weight that is one millionth.For example, if XRF shows 379 ppmw Si atoms in an (A) HSG-FP copolymer, and the comonomer used to make (A) is VTMS with a molecular weight of 148.23 g / mol, then the comonomer content is 0.20 wt%. To calculate the mol% of hydrolyzable silyl group comonomer units in the (A) HSG-FP copolymer of the at least one alkenyl-functional hydrolyzable silane comonomer used, use the calculated wt% of hydrolyzable silyl group comonomer units of (A). The formula is G=100*(p / m) / [(p / m)+(100.00wt%-p) / 28.05g / mol], where * means multiplication, G is the mole percent (mol%) of hydrolyzable silyl groups of (A), p is the weight percent of hydrolyzable silyl groups of (A), m is the molecular weight in g / mol of at least one alkenyl-functional hydrolyzable silane comonomer from which the hydrolyzable silyl groups are derived, and 28.05g / mol is the molecular weight of the monomer ethylene (H2C=CH2). For example, if the comonomer content is 2.0wt% and the comonomer is VTMS, then p=2.0wt%, m=148.23g / mol, and G=0.38mol%. If the comonomer content is 5.0wt% and the comonomer is VTMS, then p=5.0wt%, m=148.23g / mol, and G=0.99mol%. When two or more alkenyl-functional hydrolyzable silane comonomers of different molecular weights are used to produce (A), the molecular weight used in calculating the total mole % of all hydrolyzable silyl groups in (A) is the weighted average molecular weight of the comonomers. The weighting can be determined by the ratio of the amounts of comonomers fed to the GPP reactor, or by NMR spectroscopy of the (A)HSG-FP copolymer to determine the relative amounts of the different comonomer units in the (A)HSG-FP copolymer when each hydrolyzable silyl group is attached to a different type of carbon atom (e.g., tertiary vs. secondary carbon atom), or by Fourier transform infrared (FT-IR) spectroscopy calibrated to provide quantification of the various types of comonomers.

[0082] Working Example Alkyl-functional hydrolyzable silane 1: Vinyltrimethoxysilane (VTMS) is available from The Dow Chemical Company as XIAMETER™ OFS-6300 silane.

[0083] Polymer other than (A)1 (LLDPE(I)-1): Density is 0.921 g / cm 3 A linear low density polyethylene homopolymer with a melt index (I2) of 0.7 g / 10 min. Available from The Dow Chemical Company, Midland, Michigan, USA as DFDA-7530 NT LLDPE.

[0084] Tert-Butyl Peroxyacetate PA, Luperox 7M75, Trigonox F-C50 from Arkema.

[0085] Moisture Scavenger (E)-1: Octyltriethoxysilane (OTES) available as PROSIL™ 9202 from SiVance LLC, a Milliken Company.

[0086] A process for preparing HSG-FP copolymer. A stirred autoclave reactor having a capacity of 545 milliliters (mL) is charged with a mixture of ethylene, an alkenyl-functional hydrolyzable silane (e.g., vinyltrimethoxysilane (VTMS)), and propylene used as a chain transfer agent. An organic peroxide (e.g., a 75 wt % solution of tert-butyl peroxyacetate in an aliphatic hydrocarbon) is added at a loading of 0.2 wt %, based on the total weight of the ethylene, alkenyl-functional hydrolyzable silane, optionally propylene, and organic peroxide. The reactor is pressurized to 193 MPa (28,000 to 28,100 pounds per square inch (psi)) and the reactor is heated to 250°C. Ethylene, an alkenyl-functional hydrolyzable silane (e.g., vinyltrimethoxysilane (VTMS)), and optionally propylene are continuously fed into the reactor, and the (A) HSG-FP copolymer made from the reactor is removed. (A) is converted into pellets by melt extrusion.

[0087] HSG-FP copolymer (A)-1 of the present invention is produced according to the HSG-FP preparation method using VTMS as the alkenyl functional hydrolyzable silane, tert-butyl peroxyacetate as the organic peroxide, and propylene under the effective process conditions shown in Table 1. It is characterized by the properties shown in Table 2.

[0088] HSG-FP copolymer (A)-2 of the present invention is produced according to the HSG-FP preparation method using VTMS as the alkenyl functional hydrolyzable silane, tert-butyl peroxyacetate as the organic peroxide, and propylene under the effective process conditions shown in Table 1. It is characterized by the properties shown in Table 2.

[0089] Comparative HSG-FP Copolymer CE1: Produced according to the HSG-FP preparation method using VTMS as the alkenyl functional hydrolyzable silane, tert-butyl peroxyacetate as the organic peroxide, and propylene under the effective process conditions shown in Table 1. Characterized by the properties shown in Table 2.

[0090] [Table 1]

[0091] [Table 2]

[0092] Comparative HSG-FP copolymer CE2: (E) with moisture scavenger, melt index (I2) 1.5 g / 10 min, density 0.922 g / cm 3 An ethylene / VTMS copolymer characterized by a nominal alkenyl-functional hydrolyzable silyl group (VTMS) comonomer content by XRF of 1.5 wt% and 0.29 mol% total. Available from The Dow Chemical Company as SI-LINK™ ACDFDB-5451NT. The crystallinity at room temperature is 46.24 wt%.

[0093] Comparison HSG-FP copolymer CE3: Melt index (I2) 1.5g / 10min, density 0.922g / cm 3 An ethylene / VTMS copolymer characterized by an alkenyl-functional hydrolyzable silyl group (VTMS) comonomer content by XRF of 1.44 wt%, and 0.28 mol% total. Available from The Dow Chemical Company as SI-LINK™ DFDA-5451 NT. The crystallinity at room temperature is 46.87 wt%.

[0094] Catalyst Masterbatch Preparation Method (Prophetic). Using a 420 mL BRABENDER mixing bowl equipped with a cam rotor, prepare a catalyst masterbatch containing (I) a polymer as the carrier resin and (B) a condensation cure catalyst. Calculate sufficient batch mass to fill 70% of the mixing bowl. Preheat the mixing bowl to a set temperature of 160°C and set the rotor speed to 25 revolutions per minute (rpm). Add half of the carrier resin to the preheated bowl and reflux the carrier resin until completely melted to obtain a melt. Then slowly add (B) the condensation cure catalyst (e.g., DBTDL or sulfonic acid) to incorporate (B) into the carrier resin melt. Then, optionally, other carrier resins, and / or (C) antioxidants (e.g., bis(4-(1-methyl-1-phenylethyl)phenyl)amine; 2,2′-thiobis(2-t-butyl-5-methylphenol; 2,2′-thiobis(6-t-butyl-4-methylphenol; tris[(4-tert-butyl-3-hydroxy-2,6-dimethylphenyl)methyl]-1,3,5-triazine-2,4,6-trione; pentaerythritol tetrakis(3-(3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl)propionate; distearyl thiodipropionate ("DSTDP"); dilauryl thiodipropionate; or 2′,3-bis[[3-[3,5-di-tert-butyl-4-hydroxyphenyl]propionate; Add additives such as (A) dimethylformamide (D) dimethyl ether (e.g., N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-hexamethylenediamine), (B) dimethyl ether (C) dimethyl ether (D) dimethyl ether (E) dimethyl ether (F) dimethyl ether (G) dimethyl ether (H) dimethyl ether (H) dimethyl ether (I ...The cut material is fed into a Brabender prep mixer / measuring head laboratory electric batch mixer equipped with a 24:1 extruder. The carrier resin is melted using a 24:1 Maddox mixing head screw and the catalyst master batch is transferred through a 20 / 40 / 20 / 40 / 20 mesh screen pack and a strand die at a screw speed of 40 rpm using a uniform set temperature profile of 160°C throughout zone 1, zone 2, zone 3 and the die. The resulting strand extrudate is ground in a Wiley mill to produce the catalyst master batch as pellets. Optionally, (E) a moisture scavenger (e.g., octyltriethoxysilane) is impregnated into the pellets.

[0095] Catalyst Masterbatch 1: A mixture of a thermoplastic ethylene polymer, a phenolic compound, and about 3 wt. % of (B) as an alkyl-substituted aryl sulfonic acid.

[0096] Catalyst Masterbatch 2: Thermoplastic ethylene polymer, a phenolic compound, and about 2.6 wt.% dibutyltin dilaurate (CH3(CH2)3)2Sn(O2C(CH2) 10 CH3)2) as mixture of (B).

[0097] Catalyst Masterbatch 3: A mixture of (B) as a thermoplastic ethylene polymer, carbon black, moisture scavenger (octyltriethoxysilane), antioxidant, stabilizer, and about 1.5 wt.% naphthalene-based sulfonic acid.

[0098] Catalyst Masterbatch 4: A mixture of (B) as a thermoplastic ethylene polymer, an antioxidant, carbon black, titanium dioxide, a stabilizer, and about 2.6 wt.% dibutyltin dilaurate.

[0099] Each thermoplastic ethylene polymer (ethylene-based polymer) used in catalyst masterbatches 1-4 independently has 51-100 wt.% ethylene monomer units and 49-0 wt.% comonomer units derived from a comonomer independently selected from 1-butene, 1-hexene, and ethyl acrylate. Each thermoplastic ethylenic polymer can independently be a polyethylene homopolymer, LDPE, LLDPE, ethylene / 1-butene copolymer, ethylene / 1-hexene copolymer, and ethylene / ethyl acrylate (EEA) copolymer.

[0100] Method for preparing moisture curable polyethylene formulations: (E)-1 Moisture scavenger octyltriethoxysilane (if used) is immersed in pellets of inventive HSG-FP copolymer (A)-1, inventive HSG-FP copolymer (A)-2, comparative HSG-FP copolymer CE1, comparative HSG-FP copolymer CE2, or comparative HSG-FP copolymer CE3 in a glass jar at 23° C. and tumble mixed for 10 minutes. The jar and its contents are then heated in a 70° C. oven for 30 minutes, the jar is removed, and its contents are tumble mixed for 10 minutes. The resulting pellets are stored at 23° C. until ready for use within 5 days. The stored pellets are tumble mixed at 23° C. for 10 minutes immediately prior to use, and then physically mixed in a plastic bag with pellets of any of Catalyst Masterbatches 1 to 4 to obtain Comparative Compositions A to F (CE-A to CE-F) shown in Table 3 below, inventive compositions IE-A to IE-E shown in Table 4 below, and inventive compositions IE-F to IE-H shown in Table 5 below.

[0101] Tape Preparation Method: Used to prepare moisture curable polyethylene compositions in the form of tapes for evaluation of ambient cure and hot creep tests. The compositions prepared according to the above method are fed into a Brabender 3 / 4 inch extruder equipped with a 25:1 double mixing zone (pineapple) screw, a 40 / 60 / 40 mesh screen pack, and a 2 inch wide head die. The extruder has a temperature profile over four zones at the head die: 150°C, 160°C, 170°C, and 170°C, with a screw speed of 60 revolutions per minute (rpm). This creates a variety of dosage forms in tape form with average thicknesses of 54 to 67 mils (1.37 to 1.70 mm).

[0102] Ambient moisture curing method. For characterization and comparison, the ambient curing conditions were controlled as follows. The tape samples produced by the tape preparation method were cured in a 23°C ± 2°C and 50% ± 2% RH environment for up to 182 days to form the cured polymer products, as shown later in Tables 3-5. The hot creep of the cured polymer products was measured according to the hot creep test method.

[0103] Hot water curing method. The tape sample produced by the tape preparation method is immersed in a water bath at 90°C ± 2°C for 20 hours as shown in Tables 3 to 5 below to form a cured polymer product. The hot creep of the cured polymer product is measured according to the hot creep test method.

[0104] Hot Creep Test Method. The degree of crosslinking, and therefore the degree of cure, is measured in test specimens of cured polymer products prepared by the moisture cure method. The test is based on the Insulated Cable Engineers Association (ICEA) power cable insulation material standard, ICEA-T-28-562-2003. Specimens are taken along the extrusion direction from tapes with thicknesses ranging from 0.762 to 2.032 mm (30 to 80 mils). Subject the test specimens to the hot creep test method at a load Wt, 200°C, in accordance with UL2556, "Test Methods for Wire and Cable (Section 7.9)". Load Wt = CA * 200 kilopascals (kPa, 29.0 pound-feet per square inch), where CA is the cross-sectional area of ​​the dog-bone sample cut from a tape specimen prepared according to the tape preparation method. Prepare three dog-bone specimens for each test material. Make two marks on the specimen at the original distance G from each other, where G = 25 + / - 2 mm. The dog-bone specimen is placed in the upper grip of the hot creep test assembly. A hanging load of 0.2 megapascals (MPa) is applied from the gripped specimen. The test assembly with the dog-bone specimen is heated at 200°C + / - 2°C for 15 minutes in a preheated circulating air oven, and then the final length D of the specimen between the marks is measured while still under load. e Measure the HCE value. Formula 1: HCE = [100*(D eCalculate the hot creep elongation (HCE) according to: (1) / (HCE-G) / G(1). Divide the elongation by the initial length to obtain the hot creep measurement as a percentage. The lower the hot creep percentage, the lower the test specimen's elongation under load, which in turn indicates a greater degree of crosslinking and therefore a greater degree of curing. Lower hot creep values ​​indicate a higher degree of crosslinking. Hot creep measurements of specimens cured by immersion in a 90°C±2°C water bath for 20 hours indicate the final degree of crosslinking in the cured product. The higher the final degree of crosslinking in the cured polymer composition, the more non-crosslinkable or non-moisture curable (e.g., only peroxide and / or light curable) polymers (e.g., other than HSG-FP copolymers (e.g., polyethylene) can be incorporated into the moisture curable polyethylene composition while the cured polymer product still achieves a satisfactory hot creep performance of 175% or less after curing.

[0105] The hot creep performance of comparative compositions A through F (CE-A through CE-F) is shown in Table 3. The hot creep performance of inventive compositions IE-A through IE-E is shown in Table 4. The hot creep performance of inventive compositions IE-F through IE-H is shown in Table 5. The hot creep percentages of the comparative examples are measured after ambient cure starting at 2, 3, and / or 4 days, and again after 7, 10, 14, 21, 28, and 35 days. The hot creep percentages of the inventive examples are measured after ambient cure starting at 1, 2, 3, and / or 4 days, and again after 7, 10, 14, 21, 28, 35, 70, 114, and 182 days (only for CE-E, measured at 70, 114, and 182 days). These hot creep percentage values ​​measured at various time intervals are available upon request. For each example, the number of days required to achieve 100% or 80% hot creep is determined by reading or interpolating values ​​from a plot of percent hot creep versus days of ambient hardening.

[0106] [Table 3]

[0107] Hot creep measurements performed on CE-E after 182 days at 23°C / 50% RH were 142% (i.e., not yet reaching the target of 100% or even 80%).

[0108] [Table 4]

[0109] [Table 5]

[0110] As shown by comparing the comparative example data in Table 2 with the inventive example data in Tables 3 and 4, the inventive compositions produced cured compositions of the invention having substantially faster crosslinking and / or a greater degree of crosslinking at 23° C., 50% RH, as shown by the shorter time required to achieve hot creep of 100% or less than 80%, as well as hot creep measurements of less than 19% after 20 hours in a 90° C. water bath, or less than 17.5% when the composition did not contain 46 wt.% LLDPE, and hot creep measurements of less than 50% when the composition contained 46 wt.% LLDPE. The faster cure in air at 23° C., 50% RH, and greater final degree of crosslinking in a 90° C. water bath is achieved by a combination of the enabling properties of the HSG-FP copolymer and the enabling properties of the composition.

[0111] The lower the % hot creep, the greater the degree of crosslinking. The greater the degree of crosslinking, the more suitable the cured polymer composition is for use as a coating layer on a cable, such as a power cable, including embodiments in which the coating layer is cured under ambient conditions. Reducing the hot creep to a value below 175% indicates a sufficient degree of crosslinking for the resulting cured polymer product to be used as a coating layer on a cable. The faster a hot creep of 175% is achieved under ambient conditions, the higher the throughput of a production operation that uses the moisture-curable polyethylene composition to create a coating layer on a cable. For example, the present application provides the following inventions. [1] A moisture-curable polyethylene composition comprising 15 to 99.99 weight percent (wt%) of (A) a (hydrolyzable silyl group)-functional polyethylene copolymer (HSG-FP copolymer), 0.01 to 5 wt% of (B) a condensation cure catalyst, and 0 to 84.99 wt% of one or more optional additives, wherein when (B) is only a dialkyltin dicarboxylate, the dialkyltin dicarboxylate is at least 0.10 wt%, and the (A) HSG-FP copolymer is a moisture-curable polyethylene composition comprising: and providing that the (A) HSG-FP copolymer is up to 99.90 wt. % of said moisture-curable polyethylene composition, all weight percentages being based on total weight and totaling 100.00 wt. % of said moisture-curable polyethylene composition, said (A) HSG-FP copolymer being composed by copolymerizing ethylene, at least one alkenyl-functional hydrolyzable silane, optionally propylene, and optionally an olefin comonomer, said copolymerization being free of a metal-containing olefin polymerization catalyst, an organic peroxide, and optionally propylene or (C 4 -C 20 ) under effective process conditions in a high pressure, high temperature (HPT) reactor containing a chain transfer agent (CTA) that is not an alpha-olefin, and the (A) HSG-FP copolymer has a total hydrolyzable silyl group content of 0.38 to 0.99 mole percent (mol%) and limits (i) to (iii): (i) a ratio of absolute z-average molecular weight to absolute weight average molecular weight (M) of 9.51 or greater; z(abs) / M w(abs) (ii) the ratio of the absolute molecular weight dispersity to the conventional molecular weight dispersity ((M z(abs) / M w(abs) ) / (M w(conv) / M n(conv) )、(M w(conv) is the conventional weight average molecular weight, and M n(conv) (iii) both (i) and (ii). [2] Limitations (i) to (xii): (i) the HPT reactor and the process for producing the (A) HSG-FP copolymer do not contain propylene, and the (A) HSG-FP copolymer does not contain propylene units derived from propylene; (ii) the HPT reactor and the process for producing the (A) HSG-FP copolymer contain from greater than 0 wt.% to a maximum of 2 wt.% propylene, based on the total mass flow rate of ethylene, at least one alkenyl-functional hydrolyzable silane, and propylene to the HPT reactor, and the (A) HSG-FP copolymer contains from greater than 0 wt.% to a maximum of 2 wt.% propylene units derived from propylene; (iii) the HPT reactor and the process for producing the (A) HSG-FP copolymer include from greater than 0 wt.% to a maximum of 2 wt.% propylene units derived from propylene; 4 -C 20 ) does not contain an alpha-olefin, and the (A) HSG-FP copolymer is 4 -C 20 ) is free of units derived from alpha-olefins; (iv) the HPT reactor and the process for producing the (A) HSG-FP copolymer comprises a process for producing a copolymer of ethylene, at least one alkenyl-functional hydrolyzable silane, and (C 4 -C 20 ) from greater than 0 wt.% to a maximum of 20 wt.% (C 4 -C 20 ) alpha-olefin, and the (A) HSG-FP copolymer comprises from greater than 0 wt.% to a maximum of 20 wt.% of (C 4 -C 20 (v) both (i) and (iii); (vi) both (i) and (iv); (vii) both (ii) and (iii); (viii) both (ii) and (iv); (ix) the (A) HSG-FP copolymer does not comprise a grafted hydrolyzable silyl group and the moisture-curable polyethylene composition does not comprise an alkenyl-functional hydrolyzable silane; (x) both (ix) and any one of the limits (i) through (viii); (xi) the effective process conditions include a reactor temperature of 175 to 400.0° C. and a reactor pressure of 34.5 to 344.7 megapascals, or (xii) both (xi) and any one of the limits (i) through (x). [3] The moisture-curable polyethylene composition according to the above [1] or [2], wherein the total hydrolyzable silyl group content of the (A) HSG-FP copolymer is 0.43 to 0.99 mol %. [4] The molecular weight dispersity of the (A) HSG-FP copolymer is within the limits (i) to (iv): (i) M z(abs) / M w(abs) (ii) ratio of (M z(abs) / M w(abs) ) / (M w(conv) / M n(conv) ), (iii) both (i) and (ii), and (iv) M between 16.2 and 18.9. z(abs) / M w(abs) and 2.3 to 3.1 (M z(abs) / M w(abs) ) / (M w(conv) / M n(conv) The moisture-curable polyethylene composition according to any one of the above [1] to [3], wherein the ratio of [5] wherein each hydrolyzable silyl group of the (A) HSG-FP copolymer is an independent group of the formula (R 2 ) m (R 3 ) 3-m is a monovalent radical of Si-, the subscript m is an integer of 1, 2, or 3, and each R 2 are independent, H, HO-, (C 1 -C 8 ) alkoxy, (C 2 -C 6 )Carboxy, phenoxy, (C 1 -C 6 ) alkyl-phenoxy, (C 1 -C 6 )Alkyl(H)N-, ((C 1 -C 6 )Alkyl) 2 N-, (C 1 -C 6 ) alkyl(H)C=NO-, or ((C 1 -C 6 )Alkyl) 2 C=NO-, and each R 3 is independent (C 1 -C 8 ) alkyl or phenyl. [6] The moisture-curable polyethylene composition according to any one of the above [1] to [5], wherein the (B) condensation curing catalyst is selected from any one of (i) to (iv): (i) a Brønsted acid, (ii) a Brønsted base, (iii) a Lewis acid, and (iv) a Lewis base. [7] The moisture-curable polyethylene composition according to any one of the above [1] to [6], comprising more than 0% by weight to 84.99% by weight in total of one or more optional additives, the additives being selected from the group consisting of additives (C) to (I): (C) antioxidants, (D) colorants, (E) moisture scavengers, (F) stabilizers for stabilizing the composition against the effects of ultraviolet light (UV stabilizers) such as hindered amine light stabilizers (HALS), (G) processing aids, (H) flame retardants, (I) polymers that are not (A), and combinations of any two or more of (C) to (I). [8] A moisture-curable polyethylene composition comprising: (A) a (hydrolyzable silyl group)-functional polyethylene copolymer (HSG-FP copolymer); (B) a condensation cure catalyst; and zero, one, or more optional additives, the moisture curability of the composition being characterized by characteristics (i) to (iv): (i) curable under ambient conditions including air, a temperature of 23° C.±2° C., and a relative humidity of 50% RH±2% RH in less than 15 days to produce a cured polymer product characterized by a hot creep percentage of 100% or less; (ii) curable under ambient conditions including air, a temperature of 23° C.±2° C., and a relative humidity of 50% RH±2% RH within 23 days to produce a cured polymer product characterized by a hot creep percentage of 80% or less. (iii) is curable by immersion in hot water at 90° C.±2° C. for 20.0 hours to produce a cured polymer product characterized by a hot creep percentage of less than 19% when the composition does not include a polymer that is not (A); or (iv) is curable by immersion in hot water at 90° C.±2° C. for 20.0 hours to produce a cured polymer product characterized by a hot creep percentage of less than 50% when the composition includes 19 weight percent linear low density polyethylene (LLDPE), all as measured by the Hot Creep Test Method. [9] A method for producing the moisture-curable polyethylene composition according to any one of the above [1] to [8], comprising: mixing (A) a melt of a (hydrolyzable silyl group)-functional polyethylene copolymer with (B) a condensation curing catalyst to obtain a molten mixture containing the melt of (A) and the condensation curing catalyst (B); and extruding the molten mixture to produce the moisture-curable polyethylene composition.

[10] A cured polymer product produced by moisture-curing the moisture-curable polyethylene composition according to any one of the above [1] to [8] to obtain a cured polymer product.

[11] An article of manufacture comprising a shaped article of the moisture-curable polyethylene composition according to any one of [1] to [8] above, or the cured polymer product according to

[10] above.

[12] A coated conductor comprising a conductive core and a polymer layer at least partially surrounding the conductive core, wherein at least a portion of the polymer layer comprises the cured polymer product described in

[10] above.

[13] A method of conducting electricity, comprising applying a voltage across the conductive core of the coated conductor of

[12] above to generate a flow of electricity through the conductive core.

Claims

1. 15 to 99.99 weight percent (wt%) of (A) a (hydrolyzable silyl group)-functional polyethylene copolymer (HSG-FP copolymer); 0.01 to 5% by weight of (B) a condensation curing catalyst, and 0-84.99% by weight of one or more optional additives A moisture-curable polyethylene composition comprising: When (B) is solely a dialkyltin dicarboxylate, said dialkyltin dicarboxylate is at least 0.10% by weight; provided that said (A) HSG-FP copolymer is up to 99.90 wt.% of the moisture-curable polyethylene composition, all wt.% being based on total weight and totaling 100.00 wt.% of said moisture-curable polyethylene composition; (A) the HSG-FP copolymer is composed by copolymerizing ethylene, at least one alkenyl-functional hydrolyzable silane, optionally propylene, and optionally an olefin comonomer; The (A) HSG-FP copolymer has a total hydrolyzable silyl group content of 0.38 to 0.99 mole percent (mol %), a melt index of 1.43 to 2.03 (measured in accordance with ASTM D1238-13 using the 190° C. / 2.16 kg condition), and limitations (i) to (iii): (i) a ratio of absolute z-average molecular weight to absolute weight average molecular weight (M z(abs) / M w(abs) , or absolute molecular weight dispersity), (ii) a ratio of absolute molecular weight dispersity to a conventional molecular weight dispersity ((M z(abs) / M w(abs) ) / (M w(conv) / M n(conv) ), (M w(conv) is the conventional weight average molecular weight, and M n(conv) is the conventional number average molecular weight) (iii) both (i) and (ii); 1. The moisture-curable polyethylene composition according to claim 1 , characterized by a molecular weight dispersity of any one of

2. Restrictions (i) to (x): (i) The (A) HSG-FP copolymer does not contain propylene units derived from propylene; (ii) the (A) HSG-FP copolymer contains from greater than 0 wt.% to a maximum of 2 wt.% propylene units derived from propylene; (iii) The (A) HSG-FP copolymer is 4 -C 20 ) does not contain units derived from alpha-olefins; (iv) the (A) HSG-FP copolymer comprises from greater than 0% to a maximum of 20% by weight of (C 4 -C 20 ) containing comonomer units derived from alpha olefins, (v) both (i) and (iii); (vi) both (i) and (iv); (vii) both (ii) and (iii); (viii) both (ii) and (iv); (ix) the (A) HSG-FP copolymer does not contain a grafted hydrolyzable silyl group, and the moisture-curable polyethylene composition does not contain an alkenyl-functional hydrolyzable silane; or (x) (ix) and any one of restrictions (i) to (viii); 2. The moisture-curable polyethylene composition according to claim 1, characterized in that

3. 3. The moisture-curable polyethylene composition according to claim 1, wherein the total hydrolyzable silyl group content of the HSG-FP copolymer (A) is 0.43 to 0.99 mol %.

4. The molecular weight dispersity of the (A) HSG-FP copolymer is within the limits (i) to (iv): (i) M of 10.5 to 21.0 z(abs) / M w(abs) The ratio of (ii) a M z(abs) / M w(abs) ) / (M w(conv) / M n(conv) ) ratio, (iii) both (i) and (ii); (iv) M of 16.2 to 18.9 z(abs) / M w(abs) and a ratio of (M z(abs) / M w(abs) ) / (M w(conv) / M n(conv) ) ratio, 4. The moisture-curable polyethylene composition according to claim 1, wherein the polyethylene composition is a polyethylene terephthalate-based ...

5. Each hydrolyzable silyl group of the (A) HSG-FP copolymer is independently represented by the formula (R 2 ) m (R 3 ) 3-m is a monovalent group of Si-, the subscript m is an integer of 1, 2, or 3; Each R 2 are independently H, HO-, (C 1 -C 8 ) alkoxy, (C 2 -C 6 ) carboxy, phenoxy, (C 1 -C 6 ) alkyl-phenoxy, (C 1 -C 6 ) alkyl(H)N-, ((C 1 -C 6 ) alkyl) 2 N-, (C 1 -C 6 ) alkyl(H)C=NO-, or ((C 1 -C 6 ) alkyl) 2 C=NO-, Each R 3 is independent (C 1 -C 8 ) alkyl or phenyl; The moisture-curable polyethylene composition according to any one of claims 1 to 4.

6. The condensation curing catalyst (B) is selected from the group consisting of (i) to (iv): (i) Bronsted acids, (ii) a Bronsted base, (iii) a Lewis acid, (iv) Lewis bases, The moisture-curable polyethylene composition according to any one of claims 1 to 5, wherein the moisture-curable polyethylene composition is selected from any one of the following:

7. (A) The composition comprises 15% by weight or more and less than 99.99% by weight of the HSG-FP copolymer and from 0% by weight to 84.99% by weight of the one or more optional additives in total, the one or more optional additives being selected from the group consisting of additives (C) to (I): (C) an antioxidant, (D) a colorant, (E) a moisture scavenger, (F) stabilizers for stabilizing the composition against the effects of ultraviolet light (UV stabilizers), such as hindered amine light stabilizers (HALS); (G) processing aids, (H) a flame retardant, (I) a polymer that is not (A), and A combination of any two or more of (C) to (I); The moisture-curable polyethylene composition according to any one of claims 1 to 6, selected from

8. A process for producing a moisture-curable polyethylene composition according to any one of claims 1 to 7, comprising the steps of: A process for copolymerizing ethylene, at least one alkenyl-functional hydrolyzable silane, optionally propylene, and optionally an olefin comonomer, said copolymerization being free of a metal-containing olefin polymerization catalyst and free of an organic peroxide, and optionally propylene or (C 4 -C 20 ) in a reactor containing a chain transfer agent (CTA) that is not an alpha-olefin; (A) mixing a melt of a (hydrolyzable silyl group)-functional polyethylene copolymer with (B) a condensation curing catalyst to obtain a molten mixture comprising a melt of (A) and the (B) condensation curing catalyst; extruding the molten mixture to form a moisture curable polyethylene composition. A method comprising:

9. A cured polymer product produced by moisture curing the moisture-curable polyethylene composition of any one of claims 1 to 7 to obtain a cured polymer product.

10. 10. An article of manufacture comprising a shaped article of the moisture-curable polyethylene composition of any one of claims 1 to 7, or the cured polymer product of claim 9.

11. 10. A coated conductor comprising a conductive core and a polymer layer at least partially surrounding the conductive core, at least a portion of the polymer layer comprising the cured polymer product of claim 9.

12. 12. A method of conducting electricity comprising applying a voltage across the conductive core of the coated conductor of claim 11 to cause a flow of electricity through the conductive core.

Citation Information

Patent Citations

  • Silane crosslinkable copolymer composition

    JP1986195141A

  • Preparation of filled water / crosslinkable

    JP1990169644A

  • Filled hydrolyzable copolymer composition resistant to premature crosslinking reaction

    JP1994041373A

  • Polyethylene-compatible sulfonic acids as silane cross-linking catalysts

    JP1997506915A

  • Polymer composition for a layer of layer elements

    JP2017534698A